ANALISIS FAKTOR RISIKO KEJADIAN ANEMIA PADA IBU HAMIL: LITERATUR REVIEW - Ambar Dwi Retnoningrum; Puji Astutik; Ike Nurrochmawati; Asasih Villasari (LPPM STIKes SATRIA BHAKTI NGANJUK, 2025)
Anemia due to iron deficiency in the mother can impact the growth anddevelopment of the fetus/baby during and after pregnancy. Anemia remains a major publichealth problem, and the world is currently far from the global target of reducing anemia. Thepurpose of this study was to determine various risk factors for anemia in pregnant women.Method : Research method with literature review, secondary data sources (Google Scholar,Pubmed Central)